O código de trânsito brasileiro na educação ambiental em municípios - Santos, Ederson dos (2014)
This work had as its theme the study of Brazilian Traffic Code relating to environmental issues. This study aimed to identify this law related to the protection of environmental health analyzing legal provisions related to noise pollution, solid waste disposal by potential users of public roads causing visual pollution, soil and water and air pollution devices. Care for the environment factor considered worrisome and affects everyone in everyday life. Prevention of the effects produced by the programs gases generated by vehicles that roam the land routes that threaten the quality of life by burning fuel that contributes to the greenhouse effect and endangers the health of all living beings . So that impacts are reduced if makes joint actions among government, automakers, and awareness of drivers. Pollution from traffic is a problem not only in big cities but also in smaller towns and causes various types of pollution such as noise , visual and air pollution from solid wastes that are thrown from cars on public roads causing serious consequences such as flooding . Environmental education facing the traffic on the local level as a key requirement to quality of life.